Alkaline pretreatment and response surface methodology based recombinant enzymatic saccharification and fermentation of sugarcane tops. (December 2021) - Chandrakant Khaire, Kaustubh; Suryakant Moholkar, Vijayanand; Goyal, Arun
Graphical abstract: Highlights: Alkali process can efficiently separate cellulose, xylan and alkali lignin from SCT. At optimized saccharification condition for apSCT yielded 265 mg/g reducing sugar. Glucose yield at optimized conditions was found to be 214 mg/g of apSCT. Fermentation process produced about 0.19 g of bioethanol per g of glucose. Fermentation efficiency of S. cerevisiae was found to be 37.7% Abstract: In present study, the water-soluble extractives removal prior to alkali pretreatment of sugarcane tops (SCT) was carried out. The solid alkali pretreated SCT (apSCT) recovered on Field-emission scanning electron microscopy (FE-SEM) analysis showed exposure of cellulosic fibres as compared with raw SCT. The analyses of apSCT by Fourier Transform Infrared (FT-IR) Spectroscopy, X-ray diffraction (XRD) and High performance liquid chromatography (HPLC) analysis also confirmed the enhanced cellulose content in apSCT. Optimum conditions for response surface methodology based saccharification of apSCT at 40 °C, 150 rpm were 2.14% (w/v) apSCT loading in citrate–phosphate buffer (50 mM, pH 6.0), recombinant hydrolytic enzymes (from Clostridium/Hungateiclostridium thermocellum ) loading for endo -1, 4-β-glucanase (CtCel8A) = 213.2 U/g, cellobiohydrolase (CtCBH5A) = 272.5 U/g and β-glucosidase ( Ht Bg1) = 299.8 U/g for 49.2 h. Under optimized saccharification conditions, the total reducing sugar yield was 265 mg/g (glucose 214 mg/g) of apSCT. Fermentation of produced glucose by S. cerevisiae gave 0.19 g/g glucose of bioethanol.